SKRINING KADAR HEMOGLOBIN DARAH SEBAGAI UPAYA DETEKSI DINI ANEMIA PADA SANTRIWATI PONDOK PESANTREN - Elisa Oktaviana; Winda Nurmayani (Jurnal LENTERA, 2026)
Anemia among adolescent girls remains a common health problem and may affect learning concentration, immunity, and reproductive health. One of the efforts for early detection of anemia is hemoglobin screening. This community service activity aimed to determine hemoglobin levels as an effort for early detection of anemia among female students at Zeinta Elharam Baraca Islamic Boarding School. The screening was conducted using an Easy Touch hemoglobin testing device on 30 participants. The results showed that the mean age of participants was 13.80 years, ranging from 12 to 17 years. Of the 30 students examined, 5 students (16.7%) had hemoglobin levels below normal, while 25 students (83.3%) had normal hemoglobin levels. These findings indicate that some students are still at risk of anemia and require follow-up actions such as nutrition education, periodic hemoglobin monitoring, and appropriate health interventions. Hemoglobin screening can serve as an effective initial step in the early detection of anemia among female students in Islamic boarding schools.